The Magic of Chinese Theatre: Theatre as a Ritual of Sacral Transmogrification - CHAN, Margaret (Institutional Knowledge at Singapore Management University, 2009)
Social and Staged dramas, entertainment and ritual; Chinese theatre and religion share a dialectical relationship. Ancient exorcistic rituals became dramatized to awe and inspire the audience of devotees. Eventually, exorcistic troupes had to compete among themselves to attract audiences, so that an element of entertainment came into ritual theatre. Travelling story-tellers and drama troupes went from place to place entrancing their audiences with stories of gods and heroes. The actors used costumes, props and masks, and soon the characters from these entertaining theatre shows formed a cast of gods and folk heroes in the minds of the people. A dialectical relationship between theatrical images and religious beliefs developed. Performers used iconic gestures, props, costumes and make-up to portray gods, and in turn, their convincing portrayals reaffirmed the religious beliefs held by their audiences. Theatre has historically been the ultimate didactic tool used by the Chinese. In Imperial times, the ordinary people were largely illiterate so that performance had priority over text. This privileging of performance over text continues through ritual traditions. The extent to which a Chinese audience invests a theatrical performance with truth has no parallel in the West. In Chinese ritual theatre, the suspension of disbelief that is necessary for the enjoyment of the enacted drama is taken as a leap of faith. The people see family and friends portraying gods and spirits, and believe that they are seeing the gods in the flesh. Theatre is thus a ritual of sacral transmogrification of a mortal performer into a spirit of the god embodied in the performer. This paper argues that the mask, whether of wood or paper or painted on the face, is the instrument of transmogrification. The ritual origin of all Chinese theatre, including Beijing opera, is first argued by tracing the legacy of the sacred mask from Shang times to the present. The thesis that theatre by staging the image, is a ritual of sacral transmogrification is then presented. It is argued, that the image is a metaphysical doorway that allows spirits to enter into the mortal realm. This spirit power of images is on account of their double nature; for example the statue of a god, is both a statue and the representation of the god, it is both of the real world (a clay or wooden statue) and the spirit world (it is the god). In theatre, the actor is an image with a double nature; he is both himself (a mortal man) and not himself but the character and spirit-being of the god.